2013
DOI: 10.2478/aee-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear boundary condition in electromagnetic theory – analytical scheme of formulation

Abstract: The paper presents a method of how the nonlinear boundary condition [1] may be applied in nonlinear problems of electromagnetic field theory. It is introduced for problems with nonlinear conductivity. An analytical procedure has been constructed, which seeks to reduce calculations related with the nonlinear region. In order to verify the proposed solutions, two problems have been formulated: one of linear and the other of cylindrical symmetry. These have been additionally solved by the authors’ modification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This also affects the time that will be used for the operations on the symbolic expressions. A minimal amount of sub-terms for a given time harmonic can be provided by such an implementation that will ensure that the product: (6) and sum:…”
Section: Mathematical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…This also affects the time that will be used for the operations on the symbolic expressions. A minimal amount of sub-terms for a given time harmonic can be provided by such an implementation that will ensure that the product: (6) and sum:…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…Symbolic computation in steady states can be useful in many technical genres that contain complicated mathematical calculations e.g. the author has shown that the presented implementation can be used for certain nonlinear electromagnetic field problems [5,6,7].…”
Section: Introductionmentioning
confidence: 99%